The occurrence and risk factors for first venous thromboembolism in and around pregnancy: population based cohort studies using primary and secondary care data from the United Kingdom - Abdul Sultan, Alyshah (2013)
Background: Venous thromboembolism (VTE) in one of the leading causes of maternal morbidity and mortality in high income countries. However there is a surprising shortage of evidence which allows us to accurately predict which women are at high risk which has hindered prevention to date. Therefore the aim of this thesis is to measure the occurrence of and risk factors for VTE during the antepartum and postpartum periods.